STRUKTUR PUISI KERENDAHAN HATI DAN BE THE BEST OF WHATEVER YOU ARE: KAJIAN SASTRA BANDING - Muhammad Jayyid Jiddan; Melinia Asmaradini; Nevifah Bella Hanissa; Sayyidatus Syarifah (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2022)
This research is entitled Structure of Humility Poetry and Be The Best Of Whatever You Are: A Study of Comparative Literature. The purpose of this study is to describe the comparison of the physical structure and inner structure of the poem Humility and Be The Best Of Whatever You Are. This study uses a qualitative descriptive method with data collection techniques documentation on the two poems. The results of the study indicate that there are similarities and differences in the physical structure and inner structure of the two poems. Similarities in physical structure are found in typography, enjabement, rhyme and rhythm, language style, concrete words, and imagery. The similarity of the inner structure is found in the theme, tone, and atmosphere. Meanwhile, the differences in the physical structure are found in the stanzas and lines, punctuation, and diction used. Furthermore, the difference in the inner structure is in the mandate